A new balance of power in the South Caucasus: How can it lead to regional stability? - Ordukhanyan, Emil; Sukiasyan, Hayk; Shirinyan, Levon; Ananyan, Gohar (International Journal of Innovative Research and Scientific Studies, 2025)
The South Caucasus, comprising Armenia, Azerbaijan, and Georgia, remains a pivotal region at the crossroads of North-South and East-West corridors. The region is rich in energy resources and communication opportunities, and it is entangled in unresolved historical conflicts and external competition. The new situation that emerged in the region after the 2020 Nagorno-Karabakh war presumes a remaking of the new balance of power as well as the re-sharing of new zones of influence. The purpose of the study is to explore the evolving balance of power in the South Caucasus, focusing on the interplay between local actors and external stakeholders, and to evaluate the implications for regional stability. Extra-regional strategic interests and influences, as well as relevant policies and current risks of regional destabilization, are also explored. The research paper emphasizes the role of the contemporary geopolitical environment in the region by taking into consideration the key developments, regional responses, and broader implications. Comparative methods and discourse analysis of official statements are widely used in the research. Some quantitative data were also collected and analyzed for the projection of the evolving balance of power in the region. It has been concluded that the upcoming years will reveal whether the region can transition from a history of conflict to a future of cooperation, or whether new tensions will emerge from the shifting power dynamics. The region’s future stability will depend on the capacity of both local and external actors to prioritize dialogue and sustainable development over confrontation.